(untitled) (Global Journal of Management and Business Research, 2024)
Quality is a fundamental criterion for business competitiveness that currently is not limited to verifying the lack or minimal occurrence of error in the products offered since its spectrum has expanded towards more transcendental perspectives that contemplate sustainable development as well as the health and safety of workers For this reason this research is formulated in two phases namely preparation of a participatory diagnosis based on the analysis of the requirements of the ISO 9001 2015 ISO 14001 of 2015 and ISO 45001 2018 standards and their degree of implementation in a company in the mining sector in the Southwestern region of Colombia whose result showed a low level in the adoption of standards in organizational processes Based on the findings the second phase is developed consisting of the definition of the axes that should guide the implementation plan based on transversal axes based on quality standards and quality principles with a view to increasing quality and improvement keep going